The influence of pregnant women's nutrition and parenting patterns on the incidence of stunting among toddlers in Pidie Jaya - Setyani, Fitriani Wira; Juliastuti, Juliastuti; Idiana, Adri (Journal of Midwifery and Nursing, 2024)
Stunting prevention focuses on addressing the causes of nutritional problems, namely factors related to food security, especially access to nutritious food, social environment related to infant and child feeding practices (parenting), access to health services for prevention and treatment, environmental health including the availability of clean water and sanitation facilities. The objective of this study is to examine the influence of maternal BMI during pregnancy and caregiving practices on the occurrence of stunting in toddlers aged 24 to 26 months. This research employs an analytical research design using a cross-sectional approach, and statistical testing is done using the Chi Square test with a significance level of 0.05. The sample consists of 87 toddlers, selected through purposive sampling. Research findings: maternal nutritional status during pregnancy with a p-value of 0.702 (? > 0.05), exclusive breastfeeding history with p=0.001 (? < 0.05). Conclusion: maternal nutritional status during pregnancy does not have a significant effect on stunting incidence. However, parenting practices significantly affect stunting incidence in toddlers aged 24-60 months in the working area of Primary Health Care Jangka Buya.